Nuclear Receptor Coactivator 5 is Correlated with Progression in Breast Carcinoma - Xia, Erjie; Hu, Wenjing; Bhandari, Adheesh; Sindan, Namita; Huang, Duping (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Breast cancer (BC) is increasingly becoming the primary reason for death in women, which sounded the alarm. Thus, finding a novel management target for BC is imminent. Methods: The data of gene expression and clinicopathological characteristics were downloaded from The Cancer Genome Atlas (TCGA). The expression of nuclear receptor co-activator 5 (NCOA5) in 35 paired breast cancer and adjacent tissues was measured by quantitative real-time polymerase chain reaction (qRT-PCR). Univariate and Multivariate logistic regression methodology was applied to analyze the prognostic factors for lymph node metastasis (LNM). Based on the status of breast cancer-relative receptors, patients were distributed in six groups, then the Kaplan-Meier survival analysis with log-rank test was applied to investigate the involvement among the expression of NCOA5 and overall survival (OS). Results: The expression of NCOA5 in BC was greater than normal tissues when comparing the data from TCGA. This result had also been verified in our local cohort. The expression of NCOA5 was closely related to LNM, Estrogen receptor (ER) status and progesterone receptor (PR) status. The consequence of Multivariate logistic regression analysis showed that the expression of NCOA5, tumor size, ER status and clinical stage was significantly associated with LN. Moreover, subgroup analyses showed that high expression of NCOA5 is an independent risk factor for OS in patients who were in ER (+) or PR (+) or maybe human epidermal growth factor receptor-2(Her-2) positive status. Conclusion: NCOA5 was significantly correlated with LNM in BC. Meanwhile, the expression of NOCA5 could predict the OS time, especially in breast cancer patients whose status of hormone receptor was positive. NCOA5 may act as a promising treatment target to shortening the treatment period and improving the prognosis of ER (+) breast cancer.
Keywords: Breast cancer